2020
DOI: 10.1002/eji.202048851
|View full text |Cite
|
Sign up to set email alerts
|

The thioredoxin‐1 inhibitor Txnip restrains effector T‐cell and germinal center B‐cell expansion

Abstract: Thioredoxin‐1 (Trx1) is a vital component for cellular redox homeostasis. In T cells, Trx1 donates electrons for the de novo synthesis of deoxyribonucleotides to allow rapid cell proliferation. The Trx‐interacting protein (Txnip) binds to the reduced Trx1 and inhibits its activity. However, the role of Txnip in adaptive immunity in vivo is unknown. Here, we show that absence of Txnip increased proliferation of effector T cells and GC B‐cell responses in response to lymphocytic choriomeningitis virus and Qβ vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…We thus examined the 50 transcripts most correlated with ZFP36L2 in Trms/Th17/Tc17 cells (ρ > 0.4, <0.2% of assessed transcripts, p < 6.1 × 10 −364 , excluding ribosomal or mitochondrial transcripts; Table S5 ) for prior biological evidence of immune pathway restriction. Strikingly, many inflammation-suppressing genes that we noted earlier as downregulated in psoriatic T cells were found in this set, including ZFP36 , SOCS1 , SOCS3 , CCL22 , and CD69 , as well as the global quiescence enforcers BTG1 39 and TXNIP 40 ( Figure 4 A). We thus termed these genes, which appear coherently suppressed in the highest cytokine-expressing single Th17/Tc17 cells, the ZFP36L2 inflammation-suppressive transcriptional program, or ZIST .…”
Section: Resultsmentioning
confidence: 58%
“…We thus examined the 50 transcripts most correlated with ZFP36L2 in Trms/Th17/Tc17 cells (ρ > 0.4, <0.2% of assessed transcripts, p < 6.1 × 10 −364 , excluding ribosomal or mitochondrial transcripts; Table S5 ) for prior biological evidence of immune pathway restriction. Strikingly, many inflammation-suppressing genes that we noted earlier as downregulated in psoriatic T cells were found in this set, including ZFP36 , SOCS1 , SOCS3 , CCL22 , and CD69 , as well as the global quiescence enforcers BTG1 39 and TXNIP 40 ( Figure 4 A). We thus termed these genes, which appear coherently suppressed in the highest cytokine-expressing single Th17/Tc17 cells, the ZFP36L2 inflammation-suppressive transcriptional program, or ZIST .…”
Section: Resultsmentioning
confidence: 58%
“…The increased expression of these genes is therefore in line with a deregulation of CD4+ T cells in active CeD. In the pre-diagnostic marker category, the top genes were associated to diverse functions, such as thioredoxin interacting protein TXNIP (a regulator of cellular redox state whose function in CD4+ T cells seems to affect the proliferation of effector T cells) ( 34 ), and IL32 (previously associated with the progression of various inflammatory disorders including inflammatory bowel disease and gastric inflammation) ( 35 , 36 ).…”
Section: Resultsmentioning
confidence: 91%
“…Previous studies have shown that biological stimuli induced cells to produce a large amount of ROS, and the increased levels of ROS disrupted the intracellular TRX–TXNIP balance [ 62 ]. TXNIP was a pivotal endogenous negative regulator of cellular redox balance [ 22 , 63 , 64 ] that was highly expressed in immune cells and played a role in regulating lymphocyte cycle progression and proliferation in the immune system [ 62 , 65 ]. Sheng-Min Hsu, et al have confirmed suppression of the ROS could alleviate EAU [ 21 ].…”
Section: Discussionmentioning
confidence: 99%